Protecting the health and safety of the paramedic workforce in Australia: The role of cohort studies with new recruits. (31st May 2021) - Reynolds, Amy C; Crowther, Meagan E; Ferguson, Sally A; Paterson, Jessica L; Howie, Chris; Adams, Robert J
Abstract: Research related to the paramedic workforce is increasing, particularly given the associations with physical and mental health outcomes. However, it is clear that the evidence base to support future paramedic workforce initiatives lacks longitudinal data in cohorts of paramedics. We identify gaps in the epidemiological evidence base for this workforce, and provide insight into the role that prospective cohorts can, and should, play in future research in the paramedic workforce in order to identify health and safety changes over time, and the associations with job requirements, particularly shift work.